The optimization and characterization of titanium dioxide nanostructures coated glass surface properties for self-cleaning and anti-bacterial applications / Mohd Faizal Achoi - Achoi, Mohd Faizal (2013)
The preparation of TiDoNs was successfully prepared on the glass surface using two phases process; Phase I process is sol-gel spin-coating technique while Phase II process is new invented technique, heat sol-dispersions immersion technique. The TiDoNs coated glass surface was optimized with four different parameters in Phase I process which affects precursor molar concentration, spinning rate, annealing temperature and multilayer TiDoNs while in Phase II process affects growth temperature. An optimum sample of TiDoNs was optimized shows that the surface morphology is random distribution and uniform shape with growth of small TiDoNs thom-like structures at 100°C. The height of TiDoNs thorn is 17.5 nm and mean of particle size is 9.46 nm. It has 0.316 nm and 2.631 nm of roughness and thickness, respectively whereas, the optical properties shows that TiDoNs has transmittance at 84.03% attributed for absorption coefficients and optical band gap energy is about 25.25 a and 3.60 eV, respectively. An optimum sample of TiDoNs was then characterized for self-cleaning (SC) and antibacterial (AB) applications. For application I, the results of self-cleaning application characterized using contact analyzer (CA) shows that the working efficiency and performance of hydrophilic TiDoNs coated glass surface was drastically decreased from 68.12° to 0.35° of contact angle after 2.30 minutes. For application II, the results of antibacterial testing indicated that after 24 hours, an Escherichia coli (E. Coli ATTC 25922) species bacterial was not seen growth at the middle of TiDoNs coated glass surface but it grew away from the coated area. After 40 hours, the bacterial species was found to be dead.